Mahjabeen Dhala, 'Feminist Theology and Social Justice in Islam: A Study on the Sermon of Fatima' - Ni'mah, Ilya Syafa'atun (Journal for the academic study of religion, 2025)
Mahjabeen Dhala, Feminist Theology and Social Justice in Islam: A Study on the Sermon of Fatima. New York: Cambridge University Press, 2024, pp. 224, ISBN 978-10-0942-307-6.